A possibilidade de relativização da obrigação alimentícia quando configurado o abandono material e afetivo do ascendente requerente - Volpi, Mariana Mattos (2024)
This article deals with the possibility of relativizing the maintenance obligation on the part of children in favor of their parents, when there is previous material and emotional abandonment on the part of the parents. Its general objective is to analyze, through doctrine and jurisprudence, the legal feasibility of making the food burden more flexible in these cases. The research is relevant due to the search for legal certainty, as jurisprudence is divergent on the subject, as well as due to changes in family law that the law does not follow, such as the appreciation of affection. It is concluded that, despite the lack of a consolidated jurisprudential position, it is viable to relativize the child support obligation in favor of the parent who abandoned them in the past, since the ascendant cannot invoke the family solidarity that he previously failed to comply with, considering the his conduct as a procedure unworthy of the creditor towards debtors which justifies the exclusion of the maintenance charge.